Trajectory Control of Midcourse Guidance for Air-to-Air Missile Based on Feedback Linearization and Sliding Mode Control - Zhang, Chencheng; Tong, Zhiqiang; Liu, Hongquan; Pang, Weijian (Proceedings of ... IEEE International Conference on Unmanned Systems (Online), 2024)
To guarantee the accuracy and energy efficiency of long-distance midcourse guidance for air-to-air missile, a robust trajectory control method based on feedback linearization and sliding mode control is proposed. In guidance loop, the framework of offline trajectory optimization and online tracking control is introduced and the nominal optimal trajectory is obtained by Gauss pseudo-spectral method. In control loop, based on the fact that the velocity profile of tactical missile is untracked, the model is reduced to only depending on flight path angle and height. Furthermore, the reduced complex nonlinear dynamics are accurately linearized by feedback linearization. To overcome the multiple disturbances and parameter perturbation, sliding mode control is introduced to improve the robustness. The global asymptotic stability of the resulting control law is proved. The efficiency and robustness are verified by multiple simulations under the conditions of initial errors, random wind disturbance model, and parameter perturbation.